2018
DOI: 10.18261/issn.1891-943x-2018-02-04
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Learning Technologies and StudentEngagement in Learning Activities

Abstract: As digitalisation spreads in education, it is vital to understand its relation to student engagement. We used student diaries and observation data to approach student engagement and explore the use of learning technologies on a lesson-to-lesson basis. Results show that a less thought-through use of technologies might lead to unconsidered effects. Positive indicators of the facilitation of student engagement included making the learning process accessible and visible to teachers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 21 publications
6
32
1
2
Order By: Relevance
“…With an aim to design to facilitate engagement, the intervention was informed by the teachers' experience, engagement theory (Fredricks et al, 2004) a previous study (Bergdahl et al, 2018a). Our results support the use of the influencers suggested (ibid.)…”
Section: Design Principlessupporting
confidence: 76%
See 2 more Smart Citations
“…With an aim to design to facilitate engagement, the intervention was informed by the teachers' experience, engagement theory (Fredricks et al, 2004) a previous study (Bergdahl et al, 2018a). Our results support the use of the influencers suggested (ibid.)…”
Section: Design Principlessupporting
confidence: 76%
“…According to Winters and Mor (2008), it can be hard to bring about the sought after ' disruptive effects' to teaching and learning in TEL-interventions. The intervention started with suggestions on certain factors that could affect students engagement in learning following (Bergdahl et al, 2018a) to use learning technologies that enabled all students to participate simultaneously, and to follow the students' active engagement. During the intervention the teacher confirmed that using a forum t o post their work was highly engaging to students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, disengagement can be conceptualised in other ways than as the mere absence of engagement (Salmela-Aro et al 2017;Wang et al 2017), and may for example include absenteeism (Balfanz et al 2007;Tafelski et al 2017). Research has proposed that disengagement may be related to different kinds of triggering situations, such as notifications causing a distraction, poor design of learning activities, or too few technologies allocated to too many students (Bergdahl et al 2018a). Salmela-Aro et al (2016) reported that students could experience social pressure to be online, which may cause stress, exhaustion and feelings of inadequacy.…”
Section: Engagement and Disengagement In Technology-enhanced Learningmentioning
confidence: 99%
“…Students have reported that teachers do not offer adequate support in using digital technologies (Heerwegh et al 2016). While informal self-study can reflect an extensive use of various digital technologies for learning (Nouri 2018), several recent studies have concluded that if teachers do not support students' use of digital technologies for learning, the students may use these tools guided by their own initiative, which has been shown to be less beneficial, or even detrimental, to learning (Aesaert et al 2017;Bergdahl et al 2018a;Goldhammer et al 2016;Hatlevik et al 2015;Hietajärvi et al 2019).…”
mentioning
confidence: 99%